Electrical Properties of Carbon Dioxide Hydrate: Implications for Monitoring CO2 in the Gas Hydrate Stability Zone. Issue 15 (30th July 2021) - Stern, Laura A.; Constable, Steven; Lu, Ryan; Du Frane, Wyatt L.; Roberts, Jeffery J.
Abstract: CO2 and CH4 clathrate hydrates are of keen interest for energy and carbon cycle considerations. While both typically form on Earth as cubic structure I (sI), we find that pure CO2 hydrate exhibits over an order of magnitude higher electrical conductivity ( σ ) than pure CH4 hydrate at geologically relevant temperatures. The conductivity was obtained from frequency‐dependent impedance ( Z ) measurements made on polycrystalline CO2 hydrate (CO2 ·6.0 ± 0.2H2 O by methods here) with 25% gas‐filled porosity, compared with CH4 hydrate (CH4 ·5.9H2 O) formed and measured in the same apparatus and exhibiting closely matching grain characteristics. The conductivity of CO2 hydrate is 6.5 × 10 −4 S/m at 273K with an activation energy ( E a ) of 46.5 kJ/mol at 260–281 K, compared with ∼5 × 10 −5 S/m and 34.8 kJ/m for CH4 hydrate. Equivalent circuit modeling indicates that different pathways govern conduction in CO2 versus CH4 hydrate. Results show promise for use of electromagnetic methods in monitoring CO2 hydrate formation in certain natural settings or in CO2 /CH4 exchange efforts. Plain Language Summary: Gas hydrates are crystalline solids that resemble snow and consist of frozen water molecules forming cage‐like structures that trap individual gas molecules within. Hydrates form naturally where temperature, pressure, and sufficient gas supply combine to make them stable, such as at depth in continental shelves worldwide and in polar regions. Typically containing methane, gas hydrates are of intense interest for energy considerations as well as for their potential risk as natural hazards or to geotechnical operations, or as contributors to climate issues. CO2 hydrate, on the other hand, is a possible prospect for carbon storage efforts due in part to its greater stability range compared to methane hydrate. Here we report the surprisingly large effect of guest‐molecule composition on the electrical properties of gas hydrate. We show that pure CO2 hydrate exhibits significantly higher electrical conductivity than methane hydrate over the range of temperatures where they can both form on Earth, despite their similarities in crystal structure. Their distinct electrical signatures could aid in the monitoring of CO2 in certain remote settings. Key Points: Electrical conductivity ( σ ) of CO2 hydrate is 6.5 × 10 −4 S/m, over 1 log unit higher than CH4 hydrate at geologically relevant temperatures Activation energy of CO2 hydrate is 46.5 kJ/mol over the range −13°C–8°C, ∼33% greater than CH4 hydrate and closely comparable to ice These first‐ever σ measurements on pure CO2 hydrate show potential for geophysical monitoring of CO2 stored as hydrate in certain settings